A case report of an unusual presentation of a patient with recurrent idiopathic catatonia - Charlesworth, JEG; Ghosn, O; Hussain, N; Mahmoud, R; Goncalves, V; Godbole, M (Elsevier, 2023)
Background Catatonia-like presentations can be precipitated by multiple organic and medication-related causes. Psychiatric causes of catatonia are typically associated with underlying psychotic or mood disorders. Recurrent catatonia without other precipitating psychiatric diagnosis is rarely described. Methods We present the case of a man in his early 30′s with idiopathic recurrent catatonia, presented with patient consent. Results Our case presented in a catatonic state, having recently stopped using cannabis. No organic cause for his presentation was identified following extensive investigation and he was admitted for psychiatric assessment. During admission he slowly improved with benzodiazepine and electroconvulsive therapy (ECT) treatment, alongside psychological support. Despite near complete recovery, he significantly relapsed on 2 occasions requiring psychiatric re-admission over the subsequent 6 months. Thereafter, he had multiple relapsing episodes with decreasing severity during rehabilitative care. During admission we explored extensive differentials including mood disorders, schizophrenia or psychosis, drug abuse or poisoning, as underlying triggers for his catatonia. He had a finding of FIRDA (frontal intermittent rhythmic delta activity) on his second electroencephalogram (EEG), with no clinical correlate of seizure or structural abnormality. We found no evidence of any underlying psychiatric or organic cause for his presentation. Conclusions In contrast to classical descriptions of catatonia or recurrent catatonia, our case highlights the need for greater recognition of isolated idiopathic catatonia, as a diagnosis independent of mood disorder or schizophrenia. Furthermore, we evidence effective recovery with psychological support, benzodiazepines and ECT.